Defense Management concepts improving Indonesian Maritime Security - Saragih, Herlina JR; Barnas, Rayanda; Purwanto, Purwanto (The Republic of Indonesia Defense University, 2016)
This study aimed to analyze the concept of Indonesian Defence Management in the 21st century in the context of Indonesian Maritime Security and to determine the readiness of defence management capabilities in facing threats. Research method used is descriptive qualitative with data collection methods through in-depth interview and documentation. The results showed that in order to improve maritime security in Indonesia has not been implemented in a structured and comprehensive defense in accordance with the management perspective of the countries more advanced, especially on defense preparedness in logistics management such as the management and alutsista availability owned Indonesia